In vitro and in silico Investigations on the Anti-cancer Efficacy of Eupatorin, a Polymethoxy Flavone against Ovarian Cancer PA-1 Cell Line - Khamjan, Nizar A.; Jerah, Ahmed Ali; Habibullah, Mahmoud M; Farasani, Abdullah (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Ovarian cancer is a prominent contributor to cancer-related death among women residing in developed countries. The most of instances are discovered when the cancer has already developed, which results in dismal consequences. Surgery, chemotherapy, and radiation were the top priorities for first-line treatment in clinics. Traditional cancer treatments have a substantial risk of toxicity and cancer recurrence in females. Plant extracts can be utilized as an alternative to traditional chemotherapeutic drugs to solve these issues. According to recent research, plant extracts show anti-tumor, anti-cancer, and anti-proliferative effects on human tumor cell lines that have been cultivated, as well as an antiangiogenic impact. Aim: Eupatorin is a class of flavonoids isolated from various medicinal plants with various potent biological properties including anti-cancer, anti-inflammatory, and vasorelaxant actions. Materials and Methods: In the current investigation, the potential of Eupatorin as an anti-cancer agent for ovarian cancer was evaluated. In this study was determination of cytotoxicity using WST-1 assay, LDH release assay, and apoptotic cell death was detected through AO/EB dual staining, estimation of pro-apoptotic markers using ELISA method and in silico analysis. Results: The viability of PA-1 cells was reduced with an increased dosage of Eupatorin. The LDH level was increased with increased concentration of Eupatorin. The apoptosis markers levels were also increased when PA-1 cells were exposed to Eupatorin indicating apoptosis of cancer cells. The results showed that apoptosis was induced by Eupatorin in PA-1 cells by triggering the caspase pathway. In addition, the in silico experiment was done to examine the binding efficacy of Eupatorin with VEGF-A/ VEGFR and found that Eupatorin can bind more persistently to VEGF-A/VEGFR than apratoxin thereby preventing angiogenesis. Conclusion: All these results suggest that Eupatorin can be used as a potent anti-cancer drug for ovarian cancer.
Keywords: Eupatorin; Ovarian cancer; Apoptosis; PA-1 cells